0014 How do we eliminate occupational diseases in great britain?. (21st August 2017) - Raynal, Anne; Hermanns, Robbert
Abstract : In our view there is an inverse care law operating in Great Britain (GB), in that access to occupational health services (OHS), which are adequate to find occupational diseases (ODs) at an early enough stage to prevent progression, is accessible to only the circa 13% of the labour force 1, who are mostly at low risk 2 . This is because: There is no access to OHS through the National Health Service 2 There is no legal obligation, either on the state or on employers, to provide OD surveillance, except for circa 0.1% of the workforce 2 . There is no protection for occupational health professionals (OHPs), who are paid directly or indirectly by employers. Employers can change service providers if they receive unwelcomed reports of diseases or hazards 2, 3 Doctors who diagnose ODs are not required to report them to a compensation scheme or the Labour Regulator in GB 4 As the duty to report cases of ODs rests on employers, these are negligibly reported to the Regulator; consequently the causative workplaces are not being identified or rectified 2, 5 OHPs now spend most of their time on sickness absence/performance management cases, rather than on detecting and preventing cases of OD 2 . The result of the above is that workers in GB are unjustly denied early detection of harm to their health, with prompt compensation and the opportunity to avoid further harmful exposures. Unless action is taken to address these issues, by accurately ascertaining the distribution and addressing the determinants of ODs, their elimination will not be achieved in GB.